2018
DOI: 10.1016/j.jalz.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on ethnic and racial disparities in Alzheimer's disease and related dementias: Update and areas of immediate need

Abstract: Alzheimer's disease and related dementias (ADRDs) are a global crisis facing the aging population and society as a whole. With the numbers of people with ADRDs predicted to rise dramatically across the world, the scientific community can no longer neglect the need for research focusing on ADRDs among underrepresented ethnoracial diverse groups. The Alzheimer's Association International Society to Advance Alzheimer's Research and Treatment (ISTAART; alz.org/ISTAART) comprises a number of professional interest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
461
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 391 publications
(476 citation statements)
references
References 254 publications
14
461
1
Order By: Relevance
“…The immediate need to address ethnic and racial disparities in AD and related dementias has been the focus of a recent white paper 95 , which developed a series of recommendations for future strategies. These included targeted study recruitment and retention of diverse ethnoracial populations, generalization of instruments and analytic methods across research groups, ensuring that ethnoracial sub-group data is reported, creation of methods to reduce impact of small sample size on observations, and development of statistical models of risk and protective factors relevant to ethnoracial groups, to better refine prevalence and incidence 95 .…”
Section: Discussionmentioning
confidence: 99%
“…The immediate need to address ethnic and racial disparities in AD and related dementias has been the focus of a recent white paper 95 , which developed a series of recommendations for future strategies. These included targeted study recruitment and retention of diverse ethnoracial populations, generalization of instruments and analytic methods across research groups, ensuring that ethnoracial sub-group data is reported, creation of methods to reduce impact of small sample size on observations, and development of statistical models of risk and protective factors relevant to ethnoracial groups, to better refine prevalence and incidence 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Through 5 cohort studies, the Rush Alzheimer's Disease Center (RADC) [8][9][10] aims to conceptualize and conduct needed studies of older adults across diverse racial and ethnic groups. The foundation for partnering with older Latinxs, in particular, began with our earliest cohort study, the Religious Orders Study (ROS) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, all 5 cohorts (i.e., ROS, MAP, MARS, AACORE, and Latino Core) maintain a harmonized battery of tests, including assessments of many risk factors and cognitive and motor testing. The harmonization of data collection within the RADC addresses recent recommendations to establish a collaborative infrastructure across existing cohorts that include diverse racial and ethnic groups in an effort to address research gaps in the area [8]. Furthermore, the RADC is poised to identify whether or how baseline characteristics DOI: 10.1159/000509626 overlap or differ based on the unique personal, cultural, and historical contexts of older Latinxs -exclusively or in comparison to older non-Latinx black and/or older non-Latinx whites.…”
Section: Introductionmentioning
confidence: 99%
“…There are established differences related to ethnicity and culture in dementia prevalence and incidence, presentation, understanding of dementia, help‐seeking and service use . Evidence is also emerging about differences in neuroimaging and blood biomarkers that may have an impact on diagnosis .…”
mentioning
confidence: 99%
“…There are established differences related to ethnicity and culture in dementia prevalence and incidence, presentation, understanding of dementia, help‐seeking and service use . Evidence is also emerging about differences in neuroimaging and blood biomarkers that may have an impact on diagnosis . While there are no established differential responses to dementia medications by ethnicity, they are possible, given that 20% of new Food and Drug Administration pharmaceutical approvals in the United States had known racial or ethnic differences in effects …”
mentioning
confidence: 99%